Association between food marketing exposure and adolescents' food choices and eating behaviors - Scully, M.; Wakefield, M.; Niven, P.; Chapman, K.; Crawford, D.; Pratt, Steve; Baur, L.; Flood, V.; Morley, B. (2012)
The present study examined associations between food marketing exposure and adolescents’ food choices and reported consumption of energy-dense and nutrient-poor (EDNP) foods. A cross-sectional survey of 12,188 Australian secondary students aged 12–17 years was conducted, using a web-based self-report questionnaire. Measures included students’ level of exposure to commercial television and non-broadcast types of food marketing, whether they had tried a new product or requested a product they had seen advertised, and their reported consumption of fast food, sugary drinks and sweet and salty snacks. Results indicated greater exposure to commercial television, print/transport/school food marketing and digital food marketing were all independently associated with students’ food choices. High commercial television viewers (>2 h/day) were more likely to report higher consumption of EDNP foods (ORs ranged from 1.31 for fast food to 1.91 for sweet snacks). Some associations between digital food marketing exposure and students’ eating behaviors were found; however, print/transport/school food marketing was only related to sweet snack consumption. These study results suggest that cumulative exposure to television food advertising and other food marketing sources are positively linked to adolescents’ food choices and eating behaviors. Policy changes to restrict food marketing to young people should include both television and non-broadcast media.